Kajian Yuridis Tentang Kesadaran Warga Negara Untuk Menggunakan Hak Pilih Dalam Melaksanakan Demokrasi Pada Pemilihan Kepala Daerah - Muzayanah, Muzayanah (Jurusan Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2021)
The Republic of Indonesia is a state based on the rule of law in implementing state administration based on Pancasila and the 1945 Constitution. The administration of government with a democratic system in which the highest sovereignty is in the hands of the people and in its implementation the people elect a leader to run the government. To determine the regional leader / regional head must be carried out through regional head elections. Regional head elections are intended to continue the government which has ended its term of office. Therefore, regional head elections must be held simultaneously throughout the territory of the Republic of Indonesia. The holding of regional head elections is a big job and is the responsibility of all parties, including all citizens of the Republic of Indonesia, so that the implementation of regional head elections runs well. The regional head elections in question have been held and are the result of the hard work of various relevant state institutions that have carried out their duties and responsibilities, in this case the General Election Commission (KPU) which has held regional head elections simultaneously throughout the territory of the Unitary State of the Republic of Indonesia (NKRI). ). The 1945 Constitution of the Republic of Indonesia regulates the voting rights of citizens to participate and actively participate in determining regional leaders / regional heads who will lead in their respective territories. Citizens have the right to vote to vote at regional head elections. This is of course an awareness and responsibility as citizens so that regional leaders / regional heads are elected who are able to organize government and create prosperity and justice based on the values contained in the principles of Pancasila. The problem in this research is how a juridical study of the awareness of citizens to use their voting rights in implementing democracy in regional head elections?This research is a normative juridical research with the Library Research research method. The data collection method uses secondary data in the form of primary legal materials andÂ secondary and tertiary legal materials. The population in this study is a random population of residents / community of Pengkol hamlet, Mangunsari village, Gunung pati District, Semarang City. The results of the research show that people in this region as citizens of the Republic of Indonesia have the awareness and responsibility to exercise their voting rights in the implementation of regional head elections, especially the election for Mayor and Deputy Mayor of Semarang on December 9, 2020. Regional head elections in this region have been going well and in a conducive situation even though it was held during the Covid-19 pandemic. It is hoped that the holding of this regional head election will produce regional leaders who have reliable and quality leadership management and are able to bring the community to realize social justice for all Indonesian people.